Rapid oscillations in (TMTSF)(2)PF6 - Kornilov, A; Pudalov, V; Klehe, A; Ardavan, A; Qualls, J; Singleton, J (2006)
In order to clarify the origin of the "Rapid Oscillation" (RO) in (TMTSF)(2)PF6, we studied the magnetoresistance anisotropy in the Field-Induced Spin Density Wave (FISDW) phase. We have found that in the FISDW insulating state, the Fermi surface is not totally gapped; the remaining 2D metallic pockets are quantized in magnetic field and give rise to the RO. Decreasing temperature does not change the size and orientation of the closed pockets, rather, it causes depopulation of the delocalized states in favor of the localized ones, resulting in the disappearance of the RO.